Evaluation about Dengue knowledge of children at school age - Silva, Brenda da; Porto, Fernando Garcez; Marchionatti, Amanda; Machado, Ronaldo dos Santos; Moraes, Stêfani de; Schimidt, Julio Candido; Oliveira, Barbara; Mendes, Natália Helena; Ribas, Milene Almeida; Carvalho, Themis Goretti Moreira Leal de (ABCS Health Sciences, 2019)
Introduction: Dengue is an arbovirus, transmitted to humans through the bite of the Aedes aegypti mosquito, and which affects a large number of individuals in the world. Over the past 50 years, along with increased geographic expansion, the incidence of dengue increased approximately 30-fold. Over the years, several measures to combat dengue have been implemented and due to this factor, in 2004, there was a 290% reduction in dengue cases in relation to the previous year. Objective: To describe the knowledge of schoolchildren from Rio Grande do Sul on the subject of dengue. Methods: A quantitative descriptive study carried out with young students of the public education system of the city of Tupãnciretã, through a structured questionnaire. Results: It was evidenced that most of the students had knowledge about how dengue is transmitted, 35% believed that the mosquito female transmits the disease and 58.8% claim to be able to recognize the mosquito. A significant portion of the students believe that the mosquito bites preferentially during the day, where the main form of transmission selected was "The mosquito bites a sick person and transmits the disease to the other person" and the main symptoms were fever, headache and tiredness. Conclusion: The study showed that most of the young people have knowledge about dengue, however, there are still children and adolescents who do not know the subject, bringing to the fore the importance of this theme in health campaigns.